A oxigenioterapia hiperbárica na prevenção e no tratamento da osteorradionecrose - Okuyama, Rafaela Prado [UNESP] (2009)
The hyperbaric oxygen therapy (HBO) is a therapeutic method, used since the decade 30, its use and expansion has been increasingly exploited by several countries. The HBO causes the increase of partial pressure of oxygen in plasma, leading to greater amount of oxygen to the compromised area, contributing to vascular neoformation and the increased number of cells, facilitating the healing of injured tissues. The HBO is recognized indication for gas embolism, decompressive illness, traumatic embolism, carbon monoxide poisoning, cyanide poisoning, acute traumatic ischemia, thermal and electrical burns, ulcers of the skin, ulcers in the lower limbs resulting from diabetes, pressure ulcers by, radiodermite, osteoradionecrosis (ORN), flaps or grafts or risk involved and osteomyelitis. For each disease there is a protocol to be followed, which is the number of sessions, the pressure in atmospheres absolute and time duration of each session. After examining the literature we can conclude that the HBO was effective in prevention and treatment of osteoradionecrosis, however, its use gives more satisfactory results when used as adjuvant therapy